Effects of Diffuse Light on Radiation Use Efficiency of Two Anthurium Cultivars Depend on the Response of Stomatal Conductance to Dynamic Light Intensity - Li, Tao; Kromdijk, Johannes; Heuvelink, Ep; van Noort, F. R.; Kaiser, Elias; Marcelis, Leo F. M. (Frontiers in Plant Science, 2016)
The stimulating effect of diffuse light on radiation use efficiency (RUE) of crops is often explained by the more homogeneous spatial light distribution, while rarely considering differences in temporal light distribution at leaf level. This study investigated whether diffuse light effects on crop RUE can be explained by dynamic responses of leaf photosynthesis to temporal changes of photosynthetic photon flux density (PPFD).Two Anthurium andreanum cultivars (‘Pink Champion’ and ‘Royal Champion’) were grown in two glasshouses covered by clear (control) and diffuse glass, with similar light transmission. On clear days, diffusing the light resulted in less temporal fluctuations of PPFD. Stomatal conductance (gs) varied strongly in response to transient PPFD in ‘Royal Champion’, whereas it remained relatively constant in ‘Pink Champion’. Instantaneous net leaf photosynthesis (Pn) in both cultivars approached steady state Pn in diffuse light treatment. In control treatment this only occurred in ‘Pink Champion’. These cultivar differences were reflected by a higher RUE (8%) in ‘Royal Champion’ in diffuse light treatment compared with control, whereas no effect on RUE was observed in ‘Pink Champion’. We conclude that the stimulating effect of diffuse light on RUE depends on the stomatal response to temporal PPFD fluctuations, which response is cultivar dependent.